Algae Removal by Electro-coagulation Process, Application for Treatment of the Effluent from an Industrial Wastewater Treatment Plant - GH Azarian; AR Mesdaghinia; F Vaezi; R Nabizadeh; D Nematollahi (Tehran University of Medical Sciences, 2007)
Background: Although stabilization ponds and lagoons are suitable treatment processes due to simplicity of operation and low per capital costs, the effluents of these systems have too high of a total suspended solids concentration to be discharged into receiving waters. This problem is mainly caused by algae. In this study, an electro-coagulation reactor was examined to remove algae from the final effluent of the wastewater treatment plant belong to Bu-Ali Industrial Estates (Hamadan City).  Methods: For the continuous flow electro-coagulation reactor used in these experiments three aluminum anodes were utilized. This type of metal was selected because it could introduce the flocculation agent into the effluent, thereby algae could be removed by both mechanisms of electro-flotation and electro-flocculation. Results: The results of treatment were remarkably good and the efficiencies of total suspended solids (TSS) and chlorophyll a removal reached to as high as 99.5% and about 100% by applying a power input of about 550 W. In fact, this level of power input was needed for complete removal of algae in a low retention time of 15 minutes. Meanwhile, by applying less power input of about 100Wdm-3, the required time for a relatively same treatment was reached to 30 minutes. Conclusion: It is expected that this method which is also known as a multiple contaminants removal process will be considered as a suitable alternative for final polishing of effluents from lagoons and similar treatment systems.